Intensification of intellectual activity of personnel of enterprise consequential of intellectualization functions and management processes - Кісь, С. Я.; Процюк, В. Р. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
In the article the problem of intellectualization of management, intensification of intellectual activity personnel and their interaction to achieve positive results management. The scheme of transforming intellectual activity staff (managerial and executive) in the performance of the enterprise, which provides direct, indirect and combined-stimulating managers involved in their formation. Classic management functions considered in terms of planning, organize, motivation and control management system enterprise intellectual activity staff.